2023
DOI: 10.1002/adbi.202300404
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Trehalose Synthesis in Lepidoptera Reduces Larval Fitness

Meenakshi B. Tellis,
Sharada D. Mohite,
Vineetkumar S. Nair
et al.

Abstract: Trehalose is synthesized in insects through the trehalose 6‐phosphate synthase and phosphatase (TPS/TPP) pathway. TPP dephosphorylates trehalose 6‐phosphate to release trehalose. Trehalose is involved in metamorphosis, but its relation with body weight, size, and developmental timing is unexplored. The expression and activity of TPS/TPP fluctuate depending on trehalose demand. Thus, TPS/TPP inhibition can highlight the significance of trehalose in insect physiology. TPS/TPP transcript levels are elevated in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
0
0
Order By: Relevance
“…A consistent pattern of developmental disruption was observed. Tellis noted that trehalose levels could affect the size, weight, and metabolic homeostasis of Lepidoptera larvae during larval pupal transitions [47]. We observed that the treatment group could induce a certain abdominal segment contraction in the larvae, similar to morphological abnormalities that did not lead to death in a short time of outer epidermal loss.…”
Section: Discussionmentioning
confidence: 49%
“…A consistent pattern of developmental disruption was observed. Tellis noted that trehalose levels could affect the size, weight, and metabolic homeostasis of Lepidoptera larvae during larval pupal transitions [47]. We observed that the treatment group could induce a certain abdominal segment contraction in the larvae, similar to morphological abnormalities that did not lead to death in a short time of outer epidermal loss.…”
Section: Discussionmentioning
confidence: 49%